2000
DOI: 10.1111/j.1939-165x.2000.tb00412.x
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometric Evaluation of Canine Bone Marrow Differential Cell Counts

Abstract: Three flow cytometric techniques were evaluated for determination of differential cell counts on canine clinical bone marrow specimens. Techniques included staining bone marrow specimens with 2'7'-dichlorofluorescein (DCF) or 3,3'-dihexyloxacarbocyanine iodide (DiOC6) and evaluation of forward-angle light scatter vs. side-angle light scatter plots. Flow cytometric evaluation of bone marrow cells stained with DCF failed to separate bone marrow cells into distinct cell populations. Staining with DiOC6 resulted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 6 publications
(9 reference statements)
0
29
0
Order By: Relevance
“…Because erythroid cells have low granularity and may overlap in size with lymphoid cells, erythremic myelosis may be difficult to distinguish from lymphocytic leukemia. 13,14 Scatter plot analysis has been used for analysis of leukemias in the peripheral blood of dogs. 6,7,21 Scatter plot analysis correctly predicted the lineage of leukemic cells in 7 of 8 dogs.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Because erythroid cells have low granularity and may overlap in size with lymphoid cells, erythremic myelosis may be difficult to distinguish from lymphocytic leukemia. 13,14 Scatter plot analysis has been used for analysis of leukemias in the peripheral blood of dogs. 6,7,21 Scatter plot analysis correctly predicted the lineage of leukemic cells in 7 of 8 dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that rubriblasts and rubricytes are not lysed by this procedure. 13 After 10 minutes of incubation at room temperature, tubes were centrifuged, and the cell pellet was washed and resuspended in 1.0 mL of Dulbecco's phosphate-buffered saline solution containing 1% sheep serum and 2 mM sodium azide. The cell count was adjusted to 1 ϫ 10 7 cells/mL.…”
Section: Collection and Processing Of Blood And Bone Marrow Specimensmentioning
confidence: 99%
See 3 more Smart Citations